A sharp exponent bound for McFarland difference sets with p=2 - Ma, Siu Lun. (2009)
We show that under the self-conjugacy condition a McFarland difference set with p=2 and f≥ in an abelian group G can only exist,if the exponent of the Sylow 2-subgroups does not exceed 4.The method also works for odd p(where the exponent bound is p and is necessary and sufficient),so that we obtain a unified proof of the exponent bounds for MacFarland difference sets.We also correct a mistake in the proof of an exponent bound for (320,88,24)-difference sets in a previous paper.